Rhein and polydimethylsiloxane functionalized carbon/carbon composites as prosthetic implants for bone repair applications. (4th July 2017) - Jia, Zhenzhen; Yang, Cui; Jiao, Jiajia; Li, Xinyu; Zhu, Dashuai; Yang, Yongchao; Yang, Jingyi; Che, Yongzhe; Lu, Yun; Feng, Xizeng
Abstract: A major issue in bone tissue engineering is the selection of biocompatible materials for implants, to reduce unwanted inflammatory reactions and promote cell adhesion. Bone tissue growth on suitable biomedical implants can shorten recovery and hospitalization after surgery. Therefore, a method to improve tissue–implant integration and healing would be of scientific and clinical interest. In this work, we permeated polydimethylsiloxane (PDMS) into carbon/carbon (C/C) composites (PDMS–C/C) and then coated it with 4, 5-dihydroxyanthraquinone-2-carboxylic acid (rhein) to create rhein–PDMS–C/C to increase its biocompatibility and reduce the occurrence of inflammatory reactions. We measured in vitro adhesion and proliferation of MC3T3-E1 cells and bacteria to evaluate the biocompatibility and antimicrobial properties of C/C, PDMS–C/C, and rhein–PDMS–C/C. In vivo, x-ray and micro-CT evaluation three, six and nine weeks after surgery revealed that rhein–PDMS–C/C was more effective than PDMS–C/C and C/C composite in terms of antibacterial activity, cell adhesion and tissue growth. Compared with C/C and PDMS–C/C, rhein–PDMS–C/C could be suitable for clinical applications for bone tissue engineering.